The lived experience of non-teacher trained early career school counselors when consulting with teachers - Leno, Sophia M. (My University, 2024)
School counselors recognize consultation as one of the most important functions of their services. In this study, I explored the perceptions of non-teacher trained early career school counselors during consultation with teachers. School counselors’ consultation with teachers can promote the success of the students with whom they work. While researchers have examined the impact of school counselors consulting with teachers, there is a lack of research examining the experiences of school counselors when consulting with teachers. In this transcendental phenomenological study, I explored the perceptions of non-teacher-trained early career school counselors during consultation with teachers. One primary research question guided the study: 1) How do non-teacher-trained early career school counselors describe their experiences consulting with teachers? Two subsidiary questions concerning challenges and values supported more specific inquiries: 2) What challenges do non-teacher-trained early career school counselors describe when consulting teachers? 3) What values do non-teacher-trained early career school counselors describe when consulting with teachers? The sample included 10 non-teacher trained early career school counselors using data collected through in-depth, semi-structured interviews. I employed thematic analysis to identify themes in the collected data, revealing two areas and five key themes that related to the experiences of non-teacher-trained early career school counselors. The two emergent areas were (a) the challenges of consultation and (b) the values of consultation. The themes are: feeling pressured to have all the answers; dealing with imposter syndrome; consultation as a critical factor in making all students feel seen; consultation as a mutual learning experience; and the power of relationships in consultation. Findings suggested that non-teacher-trained early career school counselors need assistance managing feelings of pressure, especially the distress brought on by teacher consultation. Non-teacher-trained school counselors need help to increase their confidence when consulting with teachers in their early careers. Findings showed that a positive relationship between the non-teacher-trained early career school counselor and the teacher increased the efficacy of consultation. Recommendations are: (a) compare imposter syndrome across different professions to better understand its uniqueness or commonality and investigate how insecurity affects consultation outcomes or student support; (b) improve consultation between early career school counselors and teachers by exploring barriers to effective consultation as a way to ensure all students receive attention and support; (c) expand on the mutual learning experiences in consultation by including different school settings and address the distinct challenges that hinder professional growth during these interactions; and, (d) focus on how school counselors can manage or improve relationships with staff that start poorly, providing resources for navigating tense connections to enhance consultation efficacy. Keywords: Early career school counselors, teacher consultation, imposter syndrome, counselor-teacher relationships, non-teacher-trained counselors
Keywords: Early career school counselors; Teacher consultation; Imposter syndrome; Counselor-teacher relationships; Non-teacher-trained counselors